Prediction of the best signal peptide for periplasmic expression of melittin peptide in Escherichia coli - Asghari Baghkheirati, Dr. Amir; Karbaschian, Elnaz; Mousavi, Seyedah Zahra; Sekhavati, Mohammad Hadi (Journal of Poultry Sciences and Avian Diseases, 2024)
Periplasmic expression of antimicrobial peptides is one of the most important issues in cloning and protein expression systems. In the present study, bioinformatics methods were used to predict the best signal peptides for periplasmic expression of the melittin peptide in Escherichia coli. Therefore, the sequence of 12 signal peptides was prepared from signal peptide databases. In order to choose the best signal peptide, periplasmic expression, sub-cellular localization site, solubility, physical, and chemical properties of signal peptides were analyzed by Signalp6, Psort, Protein-sol, PRED-TAT, and Portparam servers. Out of 12 signal peptides, six passed the Signalp6 filter, and only two passed Psort. After examining the solubility of signal peptides and investigating their physical and chemical properties, it was determined that zraP has the most favorable characteristics. Finally, it can be concluded that zraP could be considered as the best signal peptide for the melittin expression. Our results can be used for periplasmic expression of melittin in Escherichia coli host.